THE ECONOMIC IMPORTANCE OF THE DIGITAL SECTOR - Ashurova M. Kh (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information about the digital economy, its benefits, economic diversification and the impact of digital technologies on economic and social life.